2022
DOI: 10.1111/jcpe.13669
|View full text |Cite
|
Sign up to set email alerts
|

The association of sedentary behaviour and physical activity with periodontal disease in NHANES 2011–2012

Abstract: Aim: Periodontal disease is one of the most prevalent oral pathologies and a major chronic disease worldwide. Lifestyle habits such as poor nutrition and smoking have been established to contribute to the development of periodontal disease, but limited research has investigated whether physical activity and sedentary lifestyle play a role.The purpose of this study is to evaluate the association between physical activity, sedentary behaviour, and periodontal disease. Materials and Methods:We used a nationally r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 36 publications
1
18
1
Order By: Relevance
“…In one randomized controlled trial, a significant improvement in periodontal health was found after 6 months of exercise intervention in patients with type 2 diabetes 26 . Moreover, our study results are similar to those of previous studies 27,28 . Shimazaki et al 27 demonstrated that having high aerobic power estimated by maximal oxygen uptake values and low BMI was associated with a low prevalence of periodontitis indicated by the CPI among Japanese adults.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In one randomized controlled trial, a significant improvement in periodontal health was found after 6 months of exercise intervention in patients with type 2 diabetes 26 . Moreover, our study results are similar to those of previous studies 27,28 . Shimazaki et al 27 demonstrated that having high aerobic power estimated by maximal oxygen uptake values and low BMI was associated with a low prevalence of periodontitis indicated by the CPI among Japanese adults.…”
Section: Discussionsupporting
confidence: 89%
“…26 Moreover, our study results are similar to those of previous studies. 27,28 Shimazaki et al 27 demonstrated that having high aerobic power estimated by maximal oxygen uptake values and low BMI was associated with a low prevalence of periodontitis indicated by the CPI among Japanese adults. Almohamad et al 28 demonstrated that long sedentary periods were associated with periodontitis among the 2011-2012 NHANES participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic Equivalent Hours = MET score * exercise time is the formula. Based on the participants’ MET, we divided them into quintiles (METQ1-Q5) ( 22 ). Underweight (BMI = 18.5), normal weight (BMI = 18.5–24.9), overweight (BMI = 25–29.9), and obese (BMI > 30.0) were the four BMI categories ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity (PA) has been proven to be a strongly protective factor in numerous diseases, 27,28 and recently its influence on periodontitis has also been reported in animal models and in the human population 29–32 . Animal studies demonstrated that mice with no access to voluntary PA wheel or swimming exercise presented higher alveolar bone resorption 29,30 .…”
Section: Introductionmentioning
confidence: 99%